Pengaruh Kepuasan Kerja dan Lingkungan Kerja terhadap Turnover Intention Karyawan PT. Jakarta Prima Cranes - Mayangsari, Devi Mayangsari; Gandung, Muhammad (Jurnal Disrupsi Bisnis, 2024)
The success of a company is influenced by the quality of human resources contained in it. Therefore, companies need to maintain employee retention. The purpose of this study is to identify how job satisfaction and work environment partially and simultaneously affect turnover intention in PT. Jakarta Prima Cranes. The research method used in this study is a quantitative method, with an associative approach. The sampling technique used is the probability sampling technique with a simple random sampling method and a sample of 62 people. The data analysis method uses simple linear regression tests, multiple linear regression tests, correlation coefficients, determination coefficients, and partial and simultaneous hypothesis tests. The results of this study show that: Job satisfaction has a negative and significant effect on the turnover intention of employees of PT. Jakarta Prima Cranes. This is evidenced by the tcount value of -6.372 < ttable -1, 671 and the significance level of 0.000 < 0.100. The work environment has a negative and significant effect on turnover intention with a tcal value of -2.136 < ttable -1, 671 and a significance level of 0.037 < 0.100. Job satisfaction and work environment have a negative and significant effect as evidenced by the multiple linear regression equation Y = 64.277 – 0.626 X1 – 0.201 X2 and the fcalculated value of 119.720 > ftable 2.39 and the significance value of 0.000 < 0.100.